Feasibility of supervised self‐testing using an oral fluid‐based HIV rapid testing method: a cross‐sectional, mixed method study among pregnant women in rural India. Issue 1 (12th September 2016) - Sarkar, Archana; Mburu, Gitau; Shivkumar, Poonam Varma; Sharma, Pankhuri; Campbell, Fiona; Behera, Jagannath; Dargan, Ritu; Mishra, Surendra Kumar; Mehra, Sunil
Abstract : Introduction: HIV self‐testing can increase coverage of essential HIV services. This study aimed to establish the acceptability, concordance and feasibility of supervised HIV self‐testing among pregnant women in rural India. Methods: A cross‐sectional, mixed methods study was conducted among 202 consenting pregnant women in a rural Indian hospital between August 2014 and January 2015. Participants were provided with instructions on how to self‐test using OraQuick ® HIV antibody test, and subsequently asked to self‐test under supervision of a community health worker. Test results were confirmed at a government‐run integrated counselling and testing centre. A questionnaire was used to obtain information on patient demographics and the ease, acceptability and difficulties of self‐testing. In‐depth interviews were conducted with a sub‐sample of 35 participants to understand their experiences. Results: In total, 202 participants performed the non‐invasive, oral fluid‐based, rapid test under supervision for HIV screening. Acceptance rate was 100%. Motivators for self‐testing included: ease of testing (43.4%), quick results (27.3%) and non‐invasive procedure (23.2%). Sensitivity and specificity were 100% for 201 tests, and one test was invalid. Concordance of test result interpretation between community health workers and participants was 98.5% with a Cohen's Kappa (k) value of k =0.566 with p< 0.001 for inter‐rater agreement. Although 92.6% participants reported that the instructions for the test were easy to understand, 18.7% required the assistance of a supervisor to self‐test. Major themes that emerged from the qualitative interviews indicated the importance of the following factors in influencing acceptability of self‐testing: clarity and accessibility of test instructions; time‐efficiency and convenience of testing; non‐invasiveness of the test; and fear of incorrect results. Overall, 96.5% of the participants recommended that the OraQuick ® test kits should become publicly available. Conclusions: Self‐testing for HIV status using an oral fluid‐based rapid test under the supervision of a community health worker was acceptable and feasible among pregnant women in rural India. Participants were supportive of making self‐testing publicly available. Policy guidelines and implementation research are required to advance HIV self‐testing for larger populations at scale.